The Integration of the Code of Ethics and Professional Skepticism in Accounting Fraud Prevention: Systematic Literature Review - Nabilah Amalia Zahra; Yusnaini Yusnaini (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to conduct a systematic literature review on the integration of the code of ethics and professional skepticism in enhancing the effectiveness of accounting fraud prevention and detection. The persistent threat of financial statement fraud to global economic stability underscores the urgency of understanding how ethical values and auditors' critical mindsets can be unified as a primary control mechanism. Employing the Systematic Literature Review (SLR) method with the PRISMA protocol, this research analyzes 26 scientific articles from the Scopus, ScienceDirect, Sinta, and Garuda databases within the period of 2018 to 2026. Data were extracted via content analysis to map research trends, the application of Agency Theory and the Theory of Planned Behavior, as well as empirical results concerning the variables studied. The primary findings indicate that the code of ethics consistently exerts a positive influence on fraud prevention, whereas the effectiveness of professional skepticism varies according to situational factors such as auditor experience and time pressure. The integration of both is proven to be more effective than partial application, with the code of ethics serving as a moral foundation and skepticism providing the technical acuity to critically examine evidence. The conclusion of this study emphasizes that sustainable fraud prevention strategies require the simultaneous reinforcement of internalized moral values and skeptical sharpness, particularly in addressing increasingly complex fraud patterns in the digital era.